2003
DOI: 10.1111/1467-9299.00361
|View full text |Cite
|
Sign up to set email alerts
|

European governance and the transfer of ‘new’ environmental policy instruments (NEPIs) in the European Union

Abstract: This article examines the use of 'new' environmental policy instruments (NEPIs), particularly market-based instruments (for example, eco-taxes) and voluntary agreements, in the European Union (EU). It focuses on the actor motivation behind the recent increase in the adoption of new and innovative instruments in EU (and member state) environmental policies while also taking account of the external international arena. The article assesses whether new ideas put forward by policy entrepreneurs, such as member gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(89 citation statements)
references
References 24 publications
0
88
0
1
Order By: Relevance
“…Eco-labels are one type of "new" environmental policy instruments with the emphasis on the role of information about environmental impacts associated with producing, distributing, consuming and/or disposing of a product. As informational devices, eco-labels are "non-binding voluntary policy tools" [11]. Eco-labels are meant to influence consumer behavior toward buying a sound eco-labeled product.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Eco-labels are one type of "new" environmental policy instruments with the emphasis on the role of information about environmental impacts associated with producing, distributing, consuming and/or disposing of a product. As informational devices, eco-labels are "non-binding voluntary policy tools" [11]. Eco-labels are meant to influence consumer behavior toward buying a sound eco-labeled product.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In line with the general trends described above, the mode of environmental policy delivery has evolved, since the mid-1990s, to rely more on a range of new policy instruments, including economic measures, private self-regulation, and greater public and stakeholder participation in decision-making (Jordan, Wurzel, Zito, & Brückner, 2003). These instruments have been introduced in parallel with, and complementary to, more 'traditional' binding regulatory measures, however, which remain important -especially in the environmental policy field (Diedrichs et al, 2011).…”
Section: New Modes Of Environmental Governancementioning
confidence: 96%
“…Negotiated governance will, they argued, tend to trigger weaker forms of transfer, perhaps some synthesis and influence, while facilitated unilateralism will at best lead to a weak form of mutual influence (Bulmer and Padgett 2005, p. 106). Jordan et al (2003c) suggested that institutional dynamics in the EU may lead to substantial policy emulation, but may often result in weaker forms of transfer reflecting the bargaining process at the EU level and the vagaries of member state transposition and implementation. Pedersen (2007, p. 71) placed more emphasis on the subsequent process of legitimation, arguing that the ecotax innovation that occurred in Denmark, Norway and Sweden was less the recognition of the idea of taxation (something that was well established already in other sectors), but rather learning on the part of policymakers about how to frame the instruments as being legitimate and rational.…”
Section: Why Are They Selected?mentioning
confidence: 99%
“…In an attempt to cut through the thicket of cause and effect, Jordan et al (2012b) took the choice affecting variables identified by Linder and Peters (1989), and related them to three main bodies of public policy theory: ideational; institutional; and episodic (Jordan et al 2003c). They argued that each theory emphasises a slightly different aspect of 'context' in its relationship to choices.…”
Section: Environmental Politics 163mentioning
confidence: 99%
See 1 more Smart Citation